Oral Feeding Readiness Assessment in Premature Infants. Issue 2 (March 2015) - Gennattasio, Annmarie; Perri, Elizabeth A.; Baranek, Donna; Rohan, Annie
Abstract : Abstract: Oral feeding readiness is a complex concept. More evidence is needed on how to approach beginning oral feedings in premature hospitalized infants. This article provides a review of literature related to oral feeding readiness in the premature infant and strategies for promoting safe and efficient progression to full oral intake. Oral feeding readiness assessment tools, clinical pathways, and feeding advancement protocols have been developed to assist with oral feeding initiation and progression. Recognition and support of oral feeding readiness may decrease length of hospital stay and have a positive impact on reducing healthcare costs. Supporting effective cue-based oral feeding through use of rigorous assessment or evidence-based care guidelines can also optimize the hospital experience for infants and caregivers, which, in turn, can promote attachment and parent satisfaction. Abstract : Nurses who care for preterm babies should be able to assess and describe feeding performance in a way that allows other caregivers to understand an infant's strengths and challenges. A review of oral feeding readiness in the premature infant and strategies for promoting safe and efficient progression to full oral intake are presented.